Effects of Stress Coping Styles and Social Defeat on Zebrafish Behaviour and Brain Transcriptomics - Pavla Hubená; Lisa Benrejdal; David Brodin; Johanna Axling; Oly Sen Sarma; Peter Bergman; Svante Winberg (Neuroscience Bulletin, 2026)
Individuals with divergent personality traits corresponding to stress coping styles have been suggested to differ in behavioural and neural plasticity. We used a model of social defeat stress to assess the coping ability of wild zebrafish selectively bred for boldness/shyness. Behavioural tests were applied to assess parameters such as boldness/exploration, aggressiveness, and displacement behaviour. Gene expression changes in the brain were assessed via RNA sequencing. The main results show a strong effect of shyness and boldness phenotype on behaviour and the brain transcriptome. Fish of the shy line displayed significant behavioural differences, while the number of differentially-expressed genes remained low. In contrast, fish of the bold line exhibited a small effect on behaviour and pronounced changes in brain gene expression. This study highlights the importance of boldness phenotype and its influence on the response to social challenges at the behavioural and transcriptomic levels.

Evolutionary implications of size-selective mortality on the ontogenetic development of shoal cohesion: a neurochemical approach using a zebrafish, Danio rerio, harvest selection experiment - Valerio Sbragaglia; Tamal Roy; Per-Ove Thörnqvist; Jose Fernando López-Olmeda; Svante Winberg; Robert Arlinghaus (Behavioral Ecology and Sociobiology, 2022)
Size-selective mortality may evolutionarily alter life-history as well as individual behavioral and physiological traits. Moreover, size-selective mortality can affect group behavioral traits, such as shoaling and collective properties (e.g., shoal cohesion), which are relevant for finding food and reducing risk of predation. Here, we present experimental evidence using selection lines of zebrafish ( Danio rerio ) that were exposed to positive (large-harvested), negative (small-harvested), and random (control) size-selective mortality for five generations, followed by eight generations during which harvesting was halted to remove maternal effects and to study evolutionarily fixed outcomes. We investigated changes in shoal cohesion and turnover in monoamines in zebrafish through ontogeny. To that end, we repeatedly measured inter-individual distance in groups of eight fish and the turnovers of dopamine and serotonin in brains of fish from juvenile to the adult stage at 40-day intervals. We, firstly, found that shoal cohesion was overall consistent through ontogeny at group levels suggesting the presence of collective personality. Secondly, we found a decrease in shoal cohesion through ontogeny in the small-harvested and control lines, while the large-harvested line did not show any ontogenetic change. Thirdly, the selection lines did not differ among each other in shoal cohesion at any ontogenetic stage. Fourthly, dopamine turnover increased through ontogeny in a similar way for all lines while the serotonin turnover decreased in the large-harvested and control lines, but not in the small-harvested line. The large-harvested line also had higher serotonin turnover than controls at specific time periods. In conclusion, intensive size-selective mortality left an evolutionary legacy of asymmetric selection responses in the ontogeny of shoal cohesion and the underlying physiological mechanisms in experimentally harvested zebrafish in the laboratory. Significant statement The evolution of animal behavior can be affected by human activities both at behavioral and physiological levels, but causal evidence is scarce and mostly focusing on single life-stages. We studied whether and to what extent size-selective harvesting, a common selection pattern in fisheries, can be an evolutionary driver of the development of shoal cohesion during ontogeny. We used a multi-generation experiment with zebrafish to study cause-and-effects of opposing size-selection patterns. We quantified shoal cohesion, and serotonin and dopamine turnover in the brain. We found that shoal cohesion emerged as a collective personality trait and that behavioral and physiological responses were asymmetrical with respect to the opposing selection patterns.

Boldness in Zebrafish Larvae—Development and Differences between a Domesticated Lab Strain and Offspring of Wild-Caught Fish - Johanna Axling; Hampus Jakobsson; Natalia Frymus; Per-Ove Thörnqvist; Erik Petersson; Svante Winberg (Fishes, 2022)
Zebrafish (Danio rerio) are becoming one of the most important model organisms in behavioural neuroscience. It has been shown repeatedly that different zebrafish strains show large behavioural differences. These divergent behavioural profiles may have a genetic basis, but environmental factors and previous experience are also known to greatly affect the behavioural phenotype of zebrafish. It could be expected that behavioural differences at the larval stage should be less affected by environmental factors and experience. In the present study, we screened larvae of zebrafish of the AB strain and offspring of wild-caught zebrafish for boldness, using an open field test. In order to follow the behavioural development, we studied larvae at the age of 5-, 7-, 12- and 30-days post fertilization (dpf). Behaviour, as well as behavioural development, clearly differed between the larvae of the different strains. Wild larvae showed larger total distance moved than AB larvae, both at light and dark conditions. These differences were already present at 12 dpf but became more pronounced with age. Wild larvae had a greater variance compared to AB larvae for most of the variables. We have previously shown that bold and shy adult zebrafish differ in the brain expression of dopamine and opioid receptors. The results of the current study show that wild larvae display significantly higher brain expression of drd2b than AB larvae at 30 dpf, a difference that could be related to differences in activity. We did not detect any differences in the expression of opioid receptors.

Social effects on AVT and CRF systems - Tobias Backström; Per-Ove Thörnqvist; Svante Winberg (Fish Physiology and Biochemistry, 2021)
Stress and aggression have negative effects on fish welfare and productivity in aquaculture. Thus, research to understand aggression and stress in farmed fish is required. The neuropeptides arginine-vasotocin (AVT) and corticotropin-releasing factor (CRF) are involved in the control of stress and aggression. Therefore, we investigated the effect of agonistic interactions on the gene expression of AVT, CRF and their receptors in juvenile rainbow trout ( Oncorhynchus mykiss ). The social interactions lead to a clear dominant-subordinate relationship with dominant fish feeding more and being more aggressive. Subordinate fish had an upregulation of the AVT receptor (AVT-R), an upregulation of CRF mRNA levels, and higher plasma cortisol levels. The attenuating effect of AVT on aggression in rainbow trout is proposed to be mediated by AVT-R, and the attenuating effect of the CRF system is proposed to be mediated by CRF.

Effects of early rearing enrichments on modulation of brain monoamines and hypothalamic–pituitary–interrenal axis (HPI axis) of fish mahseer (Tor putitora) - Imdad Ullah; Amina Zuberi; Humaira Rehman; Zulfiqar Ali; Per-Ove Thörnqvist; Svante Winberg (Fish Physiology and Biochemistry, 2020)

Anaesthesia and handling stress effects on pigmentation and monoamines in Arctic charr - Tobias Backström; Martina Heynen; Eva Brännäs; Jan Nilsson; Svante Winberg; Carin Magnhagen (Environmental Biology of Fishes, 2017)